1979
DOI: 10.1038/281565a0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of illusory movement

Abstract: Intensive studies of visual illusion have rarely shown examples of polymorphic responses. We show here that, using figures consisting of stripes shaded from dark to light, arranged in repeating sectors, an illusion of movement can be induced in about 75% of observers when viewed peripherally. The responses of the viewers fall into four categories. This polymorphic response suggests a genetic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 2 publications
4
84
0
Order By: Relevance
“…All models of static motion illusions invoke behavior of direction-selective cells (Fraser and Wilcox, 1979;Faubert and Herbert, 1999;Kitaoka and Ashida, 2003), yet this has never been tested: the responses of direction-selective cells to static motion illusions have never been measured. To investigate whether the illusory motion in Figure 1 could be explained by the activity of direction-selective cells, we recorded from 39 directional single units in V1 and 20 units in MT of three alert, fixating macaque monkeys.…”
Section: Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…All models of static motion illusions invoke behavior of direction-selective cells (Fraser and Wilcox, 1979;Faubert and Herbert, 1999;Kitaoka and Ashida, 2003), yet this has never been tested: the responses of direction-selective cells to static motion illusions have never been measured. To investigate whether the illusory motion in Figure 1 could be explained by the activity of direction-selective cells, we recorded from 39 directional single units in V1 and 20 units in MT of three alert, fixating macaque monkeys.…”
Section: Physiologymentioning
confidence: 99%
“…The illusion produces a strong sensation of motion if fixation is maintained and the illusion is moved or flashed on and off (supplemental video 1, available at www.jneurosci.org as supplemental material), which shows that simply refreshing retinal stimulation is sufficient to elicit the illusion. The illusion is a modification of the peripheral drift illusion, a saw-tooth luminance profile that induces a weak motion illusion along the black-to-white gradient (Fraser and Wilcox, 1979;Faubert and Herbert, 1999). Kitaoka and Ashida (2003) proposed that the illusory motion in Figure 1 depends on the fact that black and white are higher contrast than dark gray and light gray (compared with the average gray of the entire display) and so produce faster responses in the visual system.…”
Section: Introductionmentioning
confidence: 99%
“…The Rotating Snakes illusion (shown in Figure 2) was discovered by Kitaoka (2003) and it depends on the local arrangement of four color regions of different luminance: black (darkest), blue (second darkest), white (lightest), yellow (second lightest) (Kitaoka & Ashida, 2003;Kuriki et al, 2008). This illusion is called the Rotating Snakes illusion and can be considered an optimized version of either the Fraser-Wilcox illusion (Fraser & Wilcox, 1979;Naor-Raz & Sekuler, 2000) or the peripheral drift illusion (Faubert & Herbert, 1999). Conway et al (2005) suggested that these responses occur in the neurons in MT (middle temporal) and Kuriki et al (2008) showed that in humans hMT+ (middle temporal complex) responds to this illusion.…”
Section: Introductionmentioning
confidence: 99%
“…More than three decades ago, Fraser and Wilcox (1979) developed a repetitive spiral arrangement of sawtooth luminance gradients that elicited illusory motion (Fig. 1 A).…”
Section: Introductionmentioning
confidence: 99%